Pengaruh penambahan sukrosa terhadap mutu sabun transparan dari ekstrak etanol herba pegagan (Centella asiatica L.) - Heru Sasongko; Andarini Siwi Mumpuni (Pharmaciana, 2017)
Centella asiatica is a kind of herbs which contains antioxidant that be trusted to overcome of various skin problems such as keloids, cellulite, and black stains. One of the additional ingredients used to make the transparent soap is sucrose or frequently called white sugar. In the process of making the transparent soap, white sugar is served to help the transparency of soap. The purpose of this research is to find out the effect of increasing the sucrose toward the degree of the transparency of the soap, stability of physical properties before and after storage for eight weeks and find out the skin response towards the soap by doing irritability test towards some respondents. Pegagan extract transparent soap is varied with the concentration of sucrose 11 %, 13%, and 15 %. The soap which is produced is conducted with a series of tests of physical characteristics include transparency, pH, water content, and the stability of the foam. The results showed that the addition of sucrose affects the level of transparency and soapy water levels and no effect on pH and foam stability. Irritation test of the respondents showed most respondents did not become irritated. The stability of the physical characteristic of the form of the soap is good because during eight weeks of the usage there are no significant